VERTICAL CENTRIFUGAL CASTING OF A HYPEREUTECTIC SILUMIN WITH COOLING OF THE MOLD AND CASTING - E. I. Marukovich; V. Yu. Stetsenko; K. N. Baranov (Литьë и металлургия, 2017)
It is shown that cooling of casting molds by water with water flow of 0,42 m3/h and internal surfaces of castings with thickness of a wall 12–14 mm with water quantity 2,5×10–4–5×10–4 m3 allows to receive procurements with completely modified microstructure without use of modifiers. External layers of the produced castings consist of the eutectic silumin with compact crystals of silicon, and internal layers – of hypereutectic silumin with crystals of high-disperse primary and compact eutectic silicon.